Experimental investigation on the thermophysical properties and solidification characteristics of n-octadecane in a spherical capsule - Shihao Cao; Xijia Zhao; Fangquan Wang; Jianwei Wang; Rongshan Yang (Case Studies in Thermal Engineering)
A thorough understanding of the thermophysical properties of phase change materials and the natural convection effect during the phase transition process is crucial for the accurate modeling and designing latent heat storage systems. However, research findings on the thermophysical properties of n-octadecane and the natural convection effect during the solidification process remain insufficient. In this study, the thermophysical properties of n-octadecane, including latent heat, thermal conductivity, density, thermal expansion coefficient and dynamic viscosity, were systematically measured under varying temperature conditions. Subsequently, a comprehensive solidification experiment of n-octadecane in a spherical capsule was conducted to assess the temporal and spatial temperature distribution characteristics and the evolution patterns of the solidification front. Finally, numerical techniques were employed to quantify the impact of natural convection. The results indicate that, the relationship between solidification mass fraction and time follows a quartic polynomial pattern. Based on the temperature curve at the central point, the solidification process of n-octadecane can be divided into four distinct stages. The first two stages account for 98.2 % of the total heat release, with natural convection primarily concentrated in the sensible heat release stage of liquid phase, contributing only 2.3 % to the entire solidification process, making its effect essentially negligible.